Penerapan Model Flipped Classroom Dengan Ragam Model Pembelajaran Kooperatif Jigsaw dan Tipe Think Pair Share - Ningsih, Mega Prani; Ramadhan, Ilham Rohman; Novitasari, Nastiti; RS, Esta Rendra (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2023)
The aim of this research is to examine the application of the flipped classroom model in various cooperative learning models, namely the Jigsaw model and the Think Pair Share (TPS) type. This research is descriptive research with a qualitative approach. Data collection techniques are carried out through observation and documentation techniques. Data analysis in this research is through the Miles Huberman Interaction model by testing the validity of the data through data triangulation techniques. The results of this research include: 1) the flipped classroom model can be applied in cooperative learning models, namely the Jigsaw model and Think Pair Share (TPS) type synchronously and asynchronously; 2) The stages in the Jigsaw model include: a) students are given the opportunity to watch videos, b) implementation of learning in class, c) lecturers facilitate discussion activities, and d) lecturers give quizzes/tests to check students' understanding of the material they have studied; 3) The stages in the Think Pair Share (TPS) type model include: a) Think stage, where the lecturer shares learning guides and resources in the form of videos/texts, students learn individually and independently; b) Pair where students choose group partners and discuss the material they have studied independently; and c) Share, namely: each group representative shares the results of their group discussion in class and the lecturer facilitates discussion activities and encourages students to be active in class discussions.